Single human B cell-derived monoclonal anti-Candida antibodies enhance phagocytosis and protect against disseminated candidiasis - Rudkin, Fiona M. (2018)
FCT Investigator IF/00033/2012. Wellcome Trust (086827, 075470, 099215, 099197 and 101873) Wellcome Trust ISSF award (105625), MRC CiC (MC_PC_14114) and MRC Centre for Medical Mycology and University of Aberdeen for funding and a Wellcome Trust Strategic Award (097377). Wellcome Trust grant 099197MA .